Organisasi sebagai Struktur Sosial dalam Perspektif Islam: Integrasi Nilai Amanah, Keadilan, dan Efisiensi di Era Digital - Purwanti Purwanti (Lembaga Yasin AlSys, 2026)
Although studies on organizations and social structures have been widely discussed in management and organizational sociology literature, research that specifically integrates an Islamic perspective, particularly the values of amanah, justice, and efficiency, within organizational contexts in the digital era remains relatively limited. This study aims to analyze organizations as social structures from an Islamic perspective and to explore the integration of the values of amanah, justice, and efficiency in organizational management amid digital transformation. The study adopts a qualitative approach with a library research design, involving analysis of primary sources comprising the Qur'an, the Sunnah, as well as classical and contemporary works in Islamic thought, management, and organizational sociology. Data were collected through documentation techniques and analyzed using thematic analysis to identify concepts, values, and patterns of integration between Islamic teachings and modern organizational practices. The findings show that amanah functions as the ethical foundation of leadership and organizational governance, justice becomes the main principle in role distribution and decision-making, and efficiency is understood as a form of professionalism and resource optimization aligned with the principle of ihsan. These findings contribute to the development of a conceptual framework for organizations grounded in Islamic values and broaden the understanding of the relevance of Islamic teachings for organizational management in the digital era. The study concludes by emphasizing the importance of integrating the values of amanah, justice, and efficiency in building sustainable, welfare-oriented organizations, and recommends that organizational leaders, educational institutions, and policymakers adopt these values as ethical and strategic foundations in modern organizational governance. The implications of this research include theoretical contributions to enriching the Islamic management literature and practical implications for developing organizations that are adaptive, ethical, and competitive in the digital era, while also opening avenues for further research on the empirical implementation of Islamic values in contemporary organizations.